Novel therapeutic strategy for obesity through the gut microbiota-brain axis: A review article - Romina Kardan; Jaber Hemmati; Mohsen Nazari; Amjad Ahmadi; Babak Asghari; Mehdi Azizi; Mansoor Khaledi; Mohammad Reza Arabestani (Babol University of Medical Sciences, 2024)
Background: The interaction between commensal bacteria and the host is essential for health and the gut microbiota-brain axis plays a vital role in this regard. Obesity as a medical problem not only affect the health of the individuals, but also the economic and social aspects of communities. The presence of any dysbiosis in the composition of the gut microbiota disrupts in the gut microbiota-brain axis, which in turn leads to an increase in appetite and then obesity. Because common treatments for obesity have several drawbacks, the use of microbiota-based therapy in addition to treatment and prevention of obesity can have other numerous benefits for the individual. In this review, we intend to investigate the relationship between obesity and the gut microbiota-brain axis as well as novel treatment strategies based on this axis with an emphasis on gut microbiota.